2010
DOI: 10.1073/pnas.1004702107
|View full text |Cite|
|
Sign up to set email alerts
|

Unique characteristics of Ca 2+ homeostasis of the trans -Golgi compartment

Abstract: Taking advantage of a fluorescent Ca 2+ indicator selectively targeted to the trans -Golgi lumen, we here demonstrate that its Ca 2+ homeostatic mechanisms are distinct from those of the other Golgi subcompartments: ( i ) Ca 2+ uptake depends exclusively on the activity of the secretory pathway Ca 2+ ATPase1 (SPCA1), whereas the sarco-endoplasmic reticulum Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(144 citation statements)
references
References 43 publications
(47 reference statements)
6
130
1
7
Order By: Relevance
“…To determine whether PS influences resting [Ca 2ϩ ] Golgi or ionomycin-induced Ca 2ϩ release from the Golgi, we employed D1-Golgi-cameleon (41). Basal Golgi apparatus YFP/CFP ratios were not different (p Ͼ 0.1) between the PS DKO (2.45 Ϯ 0.07) and hPS1 (2.61 Ϯ 0.07) cells (Fig.…”
Section: Ps Does Not Influence Er Ca 2ϩ Dynamics In Primary B Cells Fmentioning
confidence: 99%
“…To determine whether PS influences resting [Ca 2ϩ ] Golgi or ionomycin-induced Ca 2ϩ release from the Golgi, we employed D1-Golgi-cameleon (41). Basal Golgi apparatus YFP/CFP ratios were not different (p Ͼ 0.1) between the PS DKO (2.45 Ϯ 0.07) and hPS1 (2.61 Ϯ 0.07) cells (Fig.…”
Section: Ps Does Not Influence Er Ca 2ϩ Dynamics In Primary B Cells Fmentioning
confidence: 99%
“…GT-YC3.3 was targeted to the Golgi by incorporating the N-terminal sequence of type II galactosyltransferase, and was used to successfully detect Ca 2þ release from the Golgi upon depletion of the luminal Ca 2þ with ionomycin, a Ca 2þ ionophore, although its affinity to Ca 2þ (K d ¼ 1.5 mM) appears rather high for Golgi Ca 2þ concentrations. Later, cameleon-type Golgi GECIs with lower Ca 2þ affinities were developed: Go-D1cpv and medial Go-D1cpv localized in the trans and medial Golgi through incorporation of the N-terminal sequence of sialyl-transferase I and 1,6 n-acetyl glucosaminyl transferase, respectively (42,43). These indicators showed that Ca 2þ uptake into the Golgi depends on both secretory pathway Ca 2þ ATPase1 and sarco/endoplasmic reticulum Ca 2þ ATPase, but their activities are differently regulated between the trans and medial Golgi.…”
Section: Acidic Organellesmentioning
confidence: 99%
“…However, Cifuentes et al [10] argued that the RyR channel probably takes part in the Golgi Ca 2+ release in rat sympathetic neurons, and Lissandrona et al [11] proved that the trans -Golgi subcompartment is endowed with functional RyRs in neonatal cardiac myocytes. Therefore, it also can be confirmed that RyRs may locate on the GA; hitherto they have been discovered in trans -Golgi subcompartments.…”
Section: Ga Ca2+ Regulatorsmentioning
confidence: 99%
“…Fluorescence microscopy of the endogenous expression of SPCA1 in HeLa [46] and PC12 cells [47] also revealed its Golgi-like distribution. Furthermore, SPCA1 was found to be present in the trans -Golgi stacks and networks from human keratinocytes using immunocytochemistry and sucrose gradient centrifugation [11,47]. …”
Section: Ga Ca2+ Regulatorsmentioning
confidence: 99%